Advancing Eco-theology in Islamic Educational Framework: A Systematic Review of Indonesian Research Landscape - Saputra, Sukma Eka; Agustia, Zennanta; Kolis, Nur (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to systematically map and synthesize the research landscape on eco-theology within the framework of Islamic education in Indonesia. This study addresses this gap by identifying research trends, thematic patterns, and key findings, while highlighting the role of Islamic education in responding to contemporary ecological challenges aligned with sustainable development principles. A systematic literature review was conducted following PRISMA guidelines. Data were collected from the Scopus database, covering journal articles and conference papers published between 2020 and 2025 by Indonesian-affiliated authors. Quantitative mapping was supported using Bibliometrix (R package), while qualitative data were analyzed through reflexive thematic analysis based on Braun and Clarke’s six-phase framework. The results reveal a growing research trend, with a notable surge in publications in 2025 and an annual growth rate of 24.57%. Four dominant themes emerged: (1) integration of Islamic teachings in environmental conservation, (2) the role of religious institutions and communities, (3) internalization of eco-values through education, and (4) practical conservation efforts and outcomes. Empirical findings demonstrate that pesantren and major Muslim organizations function as key agents in translating eco-theological principles into concrete environmental actions. The review is limited to Scopus-indexed publications and Indonesian-affiliated authors, which may constrain broader generalization and international comparison. This study offers the first systematic thematic synthesis of eco-theology research in Indonesian Islamic education, providing a conceptual foundation for future comparative, policy-oriented, and sustainability-focused studies.